Examining the relationship between altered brain functional connectome and disinhibition across 33 impulsive and compulsive behaviours. (February 2022) - Chye, Yann; Suo, Chao; Romero-Garcia, Rafael; Bethlehem, Richard A.I.; Hook, Roxanne; Tiego, Jeggan; Goodyer, Ian; Jones, Peter B.; Dolan, Ray; Bullmore, Edward T.; Grant, Jon E.; Yücel, Murat; et al.
Abstract : Impulsive and compulsive problem behaviours are associated with a variety of mental disorders. Latent phenotyping indicates the expression of impulsive and compulsive problem behaviours is predominantly governed by a transdiagnostic 'disinhibition' phenotype. In a cohort of 117 individuals, recruited as part of the Neuroscience in Psychiatry Network (NSPN), we examined how brain functional connectome and network properties relate to disinhibition. Reduced functional connectivity within a subnetwork of frontal (especially right inferior frontal gyrus), occipital and parietal regions was linked to disinhibition. Findings provide insights into neurobiological pathways underlying the emergence of impulsive and compulsive disorders.